STRATEGI GURU DALAM MELAKSANAKAN PENILAIAN PEMBELAJARAN PADA MASA PANDEMI COVID-19 DIKELAS RENDAH SEKOLAH DASAR - Nurhasanah, Ana; Adya Pribadi, Reksa; Sulysiyah, Siti (STKIP Subang, 2021)
This study aims to describe teacher strategies in carrying out classroom assessments during the Covid-19 pandemic in elementary schools. This research was conducted at SD Malang Nengah 1 in March 2021. Data collection in this study was carried out by means of observation, interviews, and documentation. After the data is collected, the data is analyzed qualitatively. The results of this study indicate that learning during the Covid-19 pandemic only focuses on student cognitive assessments. The strategy used by the teacher in this learning is (1) conducting face-to-face learning directly. (2) Assessment based on students' daily assignments. (3) assessment based on student experience. (4) Referring to the value of the previous semester's report cards. The results of the study, that the teacher's strategy in carrying out learning during the current pandemic is very effective for knowing the actual abilities of students, considering that the tasks given by the teacher through distance learning are not carried out by the students themselves, but are also carried out by the students.